Status of Faculty Professional Development Entities in Bangladeshi Universities: Insights from Professional Development Managers (Teacher’s World: Journal of Education and Research, 2024)
Several professional development centres have been established to develop the pedagogical knowledge and research skills of university faculty members in Bangladesh. Most professional development (PD) centres offer a wide range of training and workshop programs, mostly to early career academics. These typically involve group workshops and transmitting knowledge about how to do things. This study reports the status of professional development agencies, highlighting the purpose of the centres, how they work and the challenges professional development centres face in conducting PD activities. A qualitative research approach has been followed to serve the purpose of the study. Two different data collection instruments were developed; a document review guideline and a one-to-one interview protocol were developed. Findings indicate that most PD centres are actively running their activities under dynamic leadership. PD offerings are primarily voluntary, workshop based, and related to pedagogy and research. However, teachers are reluctant towards the sessions. The study recommends foundation training for faculties linked with promotion, increment, incentives, and other facilities; allocating sufficient budget for the centre, full-time dedicated PD managers who establish active networks with foreign universities, university administration, faculties and resource persons.Teacher’s World: Journal of Education and Research, 49 (1), 187-203